Like a bridge over troubled water : an ethnography on strategies of bodily navigation of male refugees in Cape Town - Junck, Leah Davina (Langaa Research & Publishing CIG, 2018)
In spite of South Africa's progressive constitution, citizen's intolerance of non-citizens, refugees and economic migrants has escalated in recent years. What is more, xenophobic attacks are covered in the public discourse as mere episodes of crisis and often rather fuel rhetoric of national machismo than leading to an acknowledgement of the stories and experiences of people seeking refuge and being exposed to hostility on an everyday basis. This ethnography engages with the strategies employed by a group of refugee men from different African countries in surviving and stabilising their existence in the 'mother city' Cape Town in the face of precarity. It grapples with questions of how the men manage to bring about certainty in the face of unpredictability and extends its focus to the men's dreams and the modes by which these are sought to be achieved. It thereby highlights the ways in which objectifications as refugees and less-than-human are somewhat transcended by navigating spaces with care, purpose and imagination.